Demythologising the Evan Roberts Revival, 1904–1905 - Pope, Robert (The journal of ecclesiastical history, 2006)
The Welsh religious revival of 1904–5 was a remarkable event which has evoked a number of contradictory responses. These were in some ways fuelled by the content of a folk memory which often appears to be divorced from the events of the revival itself. As a result, ambiguity has surrounded the revival and particularly the contribution of Evan Roberts, probably its most interesting and colourful leader. This article explores some aspects of that folk memory and seeks to ‘demythologise’ them by drawing on accounts of the revival meetings published by those who were involved at the time.